Analysis of The Effectiveness of Fostering Social Services of Manpower and Transmigration In Improving The Welfare of Street Children In The City of Cirebon - Agus Hidayat (Politeknik Siber Cerdika Internasional, 2020)
Research conducted by the Author titled: Analysis of the Effectiveness of Social Service Development of Manpower and Transmigration in Improving the Welfare of Street Children in the City of Cirebon. Street children have negative connotations in the eyes of some people, because they are considered unsettling or disturb public order. Based on this fact, the Cirebon city government made regulation number 6 of 2009 on the Protection of Displaced Children and Children with Special Protection in the City of Cirebon. This aims to ensure the fulfillment of children's rights in order to live, grow and participate optimally in accordance with the dignity and dignity of humanity, and get protection from violence and discrimination, for the realization of quality, noble and prosperous Indonesian children. Based on the observations of the author, there are still some problems in the development of The Social Service of Manpower and Transmigration on the welfare of street children in the city of Cirebon, among others: the lack of harmony to the implementation of the program of fostering the welfare of street children among the fields in the Social Service Of Manpower and Transmigration of cirebon city. Such as the lack of frequency of counseling and coaching carried out by employees, in fact bam 40% of coaching carried out from the target that hams achieved, so that the program that hams implemented can not run as it should. In addition, there are still many problems of street children in the city of Cirebon that require serious attention from the Social Service of Manpower and Transmigration of Cirebon City. While there are several weaknesses in the development of street children, among others: There is still a mismatch of road data among the fields within the Social Service of Manpower and Transmigration of Cirebon City, such as not achieving the target of fostering street children, data shows the average achievement of children's welfare bam road 80% of the target achieved. This is due to the lack of awareness of each field to help each other in every activity of a job. The identification of this problem is: How is the effectiveness of coaching in the Social Service of Manpower and Transmigration of Cirebon City in improving the welfare of street children in the city of Cirebon? What factors determine the ineffectiveness of coaching in improving the welfare of street children in Cirebon? The purpose of this research is: To find out the effectiveness of the development of The Social Service of Manpower and Transmigration of Cirebon City in improving the welfare of street children in the city of Cirebon. And To know the factors that determine the effectiveness of belurnuya improve the welfare of street children. The research methods that the authors use are: using qualitative research methods with descriptive approaches and case studies. Through qualitative methods so that researchers can know people (subjects) personally and see them, researchers can feel what they are experiencing in the struggles of their daily society, and researchers can study groups and experiences that we may not know at all.